2021
DOI: 10.1136/bmjophth-2020-000671
|View full text |Cite
|
Sign up to set email alerts
|

Danish teleophthalmology platform reduces optometry referrals into the national eye care system

Abstract: ObjectiveThe purpose of this study was to evaluate the stratification of follow-up and referral pathways after implementation of a systematic cloud-based electronic-referral teleophthalmological service for optometry-initiated ocular posterior segment disease referrals to the Danish national eye care system.Methods and AnalysisA retrospective cohort study was conducted in the period from 1 August 2018 to 31 July 2019. Patients with suspected ocular posterior segment disease reviewed by the telemedical ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The sensitivity of fundus photography (81%) is slightly lower than that of OCT (97.5%), whereas the specificity (89.5%) is slightly higher than that of OCT (85%); however, both are superior to that of the Amsler grid . In some countries, optometry clinics provide posterior segment screening using imaging modalities such as fundus photography or OCT, after which images are interpreted in collaboration with retina specialists . These initiatives bring retinal imaging closer to the patients, allow broader access to better diagnostic methods, and help with triaging patients by urgency …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of fundus photography (81%) is slightly lower than that of OCT (97.5%), whereas the specificity (89.5%) is slightly higher than that of OCT (85%); however, both are superior to that of the Amsler grid . In some countries, optometry clinics provide posterior segment screening using imaging modalities such as fundus photography or OCT, after which images are interpreted in collaboration with retina specialists . These initiatives bring retinal imaging closer to the patients, allow broader access to better diagnostic methods, and help with triaging patients by urgency …”
Section: Discussionmentioning
confidence: 99%
“…In some countries, optometry clinics provide posterior segment screening using imaging modalities such as fundus photography or OCT, after which images are interpreted in collaboration with retina specialists . These initiatives bring retinal imaging closer to the patients, allow broader access to better diagnostic methods, and help with triaging patients by urgency …”
Section: Discussionmentioning
confidence: 99%
“…Danish teleophthalmology platform is a good example to overcome this challenge. 36 It was a real-world, large-scale, e-health based teleophthalmologic model. The authors of this study point out the requirement of an e-health model due to the dramatically risen eye care patients and concomitant referral system emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Danish teleophthalmology platform is a good example to overcome this challenge 36 . It was a real-world, large-scale, e-health based teleophthalmologic model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in glaucoma care, referral filtering schemes have been implemented to ‘triage’ low‐risk patients by optometrists with higher training and certification 6 through repeating, enhancing or refining the findings from the community eye examination before deciding whether onward referral to the HES is appropriate. More recently, with the advancement of ocular imaging, there has also been a focus on the implementation of teleophthalmology services for asynchronous referral review and triage, which has been shown to reduce the number of unnecessary referrals for retinal disease from entering the HES 7,8 . Furthermore, the significant surge in the development of artificial intelligence (AI) for medical imaging 9,10 has highlighted a potential for its use in a range of applications including eye care.…”
Section: Introductionmentioning
confidence: 99%